The effects of orthodontic treatment on personal dental expenditures in South Korea: a follow-up study using Korean health panel survey - Bo-Ra Kim; Han-A Cho; Hosung Shin (BMC, 2022)
Abstract Background This study aimed to investigate the effects of orthodontic treatment on cumulative out-of-pocket (OOP) expenditures for up to 8 years and the factors contributing to changes in individual OOP dental expenses. Methods The data of adults aged ≥19 years, 218 with experience of orthodontic treatment (OT group) and 654 without experience of orthodontic treatment (non-OT group) were extracted from the Korea Health Panel Survey between 2009 and 2017 using the propensity score matching method. The total personal OOP expenditure for dental care incurred after orthodontic treatment in the OT group and that incurred in the matched non-OT group were calculated. Since dependent variables, cumulative dental expenditures, were continuous with excess zeros, Tweedie compound Poisson linear models were used to explore the influence of orthodontic treatment experience and demographic and socioeconomic factors, including private insurance, on per capita OOP dental expenditures. Results The OT group had socioeconomic characteristics distinct from those of general dental patients. The Box-Cox transformed per capita OOP expenditures for dental care in the OT group were lower than those in the non-OT group (P < 0.05). When all covariates were held constant, the non-OT group spent 1.4-times more on OOP dental expenditures, but this was not statistically significant (P > 0.1). The data from those with higher incomes revealed the opposite trend (P < 0.05), while the other covariates were not statistically significant. Conclusions Orthodontic treatment had no positive or negative effect on future oral care use. This finding is similar to the inconsistent results of previous clinical studies on oral health and orthodontic treatment.